Peran Tutor dalam Meningkatkan Kompetensi Peserta Didik pada Kursus Menjahit melalui Pendekatan Andragogi di SKB Gudo Jombang - Aprilia, Dita; Artha, I Ketut Atmaja Jhony (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2024)
In the era of globalization, enhancing human resource quality is increasingly crucial. The sewing course at Gudo Jombang Learning Center requires the implementation of an andragogical learning approach by tutors to accommodate the learning characteristics of adult learners, particularly housewives. This study aims to describe, analyze, and identify the role of tutors, the application of the andragogical approach, and the challenges faced in improving learners' competencies in the sewing course at Gudo Jombang Leraning Center. This research uses a descriptive qualitative approach with data collection techniques of in-depth interviews, participant observation and documentation. The results of the research, (1) Tutors at Gudo Jombang Learning Center actively fulfill their roles as informers, organizers, motivators, facilitators, directors, mediators, initiators, and evaluators in the learning process. (2) The application of andragogical principles has been successful, evidenced by the improvement in learners' competencies in knowledge, skills, and attitudes. Learners demonstrated an understanding of basic sewing concepts, the ability to practice sewing techniques correctly, and a positive attitude toward learning. (3) Challenges in implementing the andragogical approach in the sewing course include limited facilities and infrastructure, decreasing attendance, varying levels of sewing experience, and suboptimal tutor andragogical skills.